Sampling of unregulated components of a two-stroke, stepped-piston engine emission - Latiff, Z. A.; Prabakaran, V.; Aziz, A. A. (2006)
High unburnt hydrocarbons (HC) emissions results in the case of carbureted two-stroke engine because of the scavenging process carried out by fresh mixture of air and fuel. Some of this air-mixture combines with the residual exhaust gas as it scavenges the cylinder. The use of lubrication oil present in the combustion process, inhibits the two-stroke engine as a mean engine to the environment. A two-stroke step-piston engine was developed to minimize these problems. The step-piston engine configurations incorporate a compression chamber which eliminates the use of crankcase compression. Therefore the usage of lubrication oil to lubricate the crankcase components could be stop. In this paper the unregulated gases namely benzene, 1,3-butadiene, toluene and methyl tertiary butyl ether (MTBE) were considered. Gas chromatography (GC) machine equipped with flame ionization detector (FID) was employed to detect the gases. A method was developed for analyzing hydrocarbon based gases. The test was fully computer guided using TotalChrom software where the results were displayed and logged automatically. Detected gas components arise from the GC were displayed qualitatively. Later the results were analyzed using Total Hydrocarbons Analysis (DHA) software for quantitative analysis. A conventional two-stroke engine was later chosen for comparative study